Phosphorylation of Influenza A Virus Matrix Protein 1 at Threonine 108 Controls Its Multimerization State and Functional Association with the STRIPAK Complex - Liu, Lu; Weber, Axel; Linne, Uwe; Shehata, Mahmoud; Pleschka, Stephan; Kracht, Michael; Schmitz, M. Lienhard; Justus Liebig University Giessen (My University, 2023)
The influenza A virus (IAV)-encoded matrix protein 1 (M1) acts as a master regulator of virus replication and fulfills multiple structural and regulatory functions in different cell compartments. Therefore, the spatiotemporal regulation of M1 is achieved by different mechanisms, including its structural and pH-dependent flexibility, differential association with cellular factors, and posttranslational modifications. Here, we investigated the function of M1 phosphorylation at the evolutionarily conserved threonine 108 (T108) and found that its mutation to a nonphosphorylatable alanine prohibited virus replication. Absent T108, phosphorylation led to strongly increased self-association of M1 at the cell membrane and consequently prohibited its ability to enter the nucleus and to contribute to viral ribonucleoprotein nuclear export. M1 T108 phosphorylation also controls the binding affinity to the cellular STRIPAK (striatin-interacting phosphatases and kinases) complex, which contains different kinases and the phosphatase PP2A to shape phosphorylation-dependent signaling networks. IAV infection led to the redistribution of the STRIPAK scaffolding subunits STRN and STRN3 from the cell membrane to cytosolic and perinuclear clusters, where it colocalized with M1. Inactivation of the STRIPAK complex resulted in compromised M1 polymerization and IAV replication. IMPORTANCE: Influenza viruses pose a major threat to human health and cause annual epidemics and occasional pandemics. Many virus-encoded proteins exert various functions in different subcellular compartments, as exemplified by the M1 protein, but the molecular mechanisms endowing the multiplicity of functions remain incompletely understood. Here, we report that phosphorylation of M1 at T108 is essential for virus replication and controls its propensity for self-association and nuclear localization. This phosphorylation also controls binding affinity of the M1 protein to the STRIPAK complex, which contributes to M1 polymerization and virus replication.
Keywords: influenza A virus; kinase; signaling; phosphorylation; STRIPAK; budding; ddc:570